Aristotle’s Rhetoric of Megawati Soekarnoputri's Political Speech at the Opening of Rakernas II PDIP - Riesardhy, Anastasia Winanti; Suryatini, Ni Wayan (MEDIASI Jurnal Kajian dan Terapan Media, Bahasa, Komunikasi, 2024)
The statement of the Chairperson of the Partai Demokrasi Indonesia Perjuangan (PDIP), Megawati Soekarnoputri, during her speech at the Second National Work Meeting in Jakarta on June 21, 2022, sparked controversy. In her speech, she made a joke about 'tukang bakso' that was considered racist. A politician should master the art of oratory. Using Aristotle's theory of rhetoric, this research is expected to provide input for both politicians and practitioners on how to use rhetoric appropriately when delivering their arguments and persuasive messages. Using qualitative content analysis, this research found that Megawati Soekarnoputri had applied the concepts of logos, pathos, and ethos in her speech. However, the research concludes that Megawati Soekarnoputri's speech has not been able to fulfill Aristotle's five laws of rhetoric.